Ten questions in sports engineering: supershoe use in distance running - Dyer, B. (Sports Engineering, 2024)
Footwear used in competitive distance running has remained relatively unchanged in nature for decades. However, such technology has recently generated controversy with the introduction of so-called `supershoes`. Such footwear appear both aesthetically and functionally different to those used prior to their introduction and their arrival coincided with a spate of distance running world records being broken. The ten questions presented in this paper address a series of issues that relate to supershoes. These include their definition, what level of performance enhancement they provide and what impact they have had in competitive sport. Furthermore, it is explored how such technology is regulated and whether it should be considered fair. Via these questions, we hope to inform readers towards a greater understanding of this form of sports technology and highlight research and engineering gaps for future work.